1976
DOI: 10.1021/bi00656a001
|View full text |Cite
|
Sign up to set email alerts
|

Topography of human plasma α1-acid glycoprotein

Abstract: Human plasma alpha1-acid glycoprotein, whose linear amino acid sequence has recently been elucidated (Schmid et al. (1973), Biochemistry 12, 2711), was further investigated with regard to its topography. Nitration of this protein and subsequent elucidation of the structures of the peptides containing modified tyrosine indicated that residues 27, 37, 78, 115, 127, and 157 are free, 50 and 91 are in an intermediate state, and 65, 74, 110, and 142 are buried. CD measurements between pH 10 and 12 demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1978
1978
1993
1993

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…At pH 13.1 the ionization was complete (26.2 mol) and the pK value obtained from this experiment for the ionization of tyrosine hydroxyl groups was 1I2-01. Schmid et al (1976) have recorded a pK value of between 11-7 and 11-9 for the alkaline denaturation of el-acid glycoprotein, measured by the changes in circular dichroism spectra, noting that the value agrees well with the apparent pK of 11 8 of the 3 tightly bonded tyrosine residues reported by Yamagami et al (1968).…”
Section: Methodssupporting
confidence: 77%
See 1 more Smart Citation
“…At pH 13.1 the ionization was complete (26.2 mol) and the pK value obtained from this experiment for the ionization of tyrosine hydroxyl groups was 1I2-01. Schmid et al (1976) have recorded a pK value of between 11-7 and 11-9 for the alkaline denaturation of el-acid glycoprotein, measured by the changes in circular dichroism spectra, noting that the value agrees well with the apparent pK of 11 8 of the 3 tightly bonded tyrosine residues reported by Yamagami et al (1968).…”
Section: Methodssupporting
confidence: 77%
“…In the presence of high concentrations of urea, both reagents modified essentially all 12 of the tyrosine residues. In a recent re-examination of the reaction of tetranitromethane with al-acid glycoprotein, Schmid et al (1976) found that 6 tyrosine residues were nitrated. They concluded that the tyrosine residues of this glycoprotein may be divided into 3 groups: one containing 6 freely reacting tyrosines, one containing 2 residues in an intermediate, partially buried state, and one containing 4 tyrosines which are buried.…”
Section: Methodsmentioning
confidence: 99%
“…However, its biological significance in these responses is still unexplained. Although the three-dimensional structure of c^S has not been determined, extensive studies of its physical properties and of the effect of chemical substitutions have helped define the topography of the molecule (Schmid et al, 1976). 5) was first isolated from human plasma independently in Winzler's laboratory (Weimer et al, 1950) and by Schmid (1953), and soon became the most completely characterized serum glycoprotein (Winzler, 1955).…”
Section: S Dj-acid Glycoproteinmentioning
confidence: 99%
“…Orosomucoid, a highly polyanionic z,-acidglycoprotein with a mol wt of 2 41 k D and an isoelectric point (pl) as low as 2.7 at physiological pH, is mainly synthesized by liver cells and it is normally present in human plasma in concentrations of 0.7-1.0 g I--* (Schmid 1989).…”
mentioning
confidence: 99%
“…T h e a,-acid-glycoprotein orosomucoid has been subject to several studies over the years and its biochemical and pharmacological characteristics have been fairly well determined, but its physiological effects have remained obscure (Routledge 1989, Schmid 1989). However, orosomucoid was discovered a few years ago, to be a modulator of the capillary permselectivity in different vascular beds (Haraldsson & Rippe 1987, Curry et al 1989, Wdhlander et al 1992), including the highly specialized glomerular capillary bed (Haraldsson et al 1992).…”
mentioning
confidence: 99%